Genetic identification of interspecific hybrid of Neotropical catfish species (Pseudoplatystoma corruscans vs. Pseudoplatystoma reticulatum) in rivers of Mato Grosso do Sul State, Brazil - Vaini, Jussara Oliveira (2014)
Hybrids of the species Pseudoplatystoma corruscans vs. Pseudoplatystoma reticulatum are extensively traded because they are more docile and precocious compared to their parents. This study aimed to identify the occurrence of hybrid 'Surubim'in rivers of the State of Mato Grosso do Sul, applying molecular techniques. Pseudoplatystoma corruscans, Pseudoplatystoma reticulatum and hybrid 'Surubim'were detected using multiplex PCR and PCR-RFLP in RAG2, GLOBIN, EF1 alpha, 18S rRNA nuclear genes, and mitochondrial 16S rRNA gene. The results revealed the presence of F-1 hybrids in rivers and the occurrence of genetic introgression, evidenced by the Post-F-1 hybrids. Furthermore, discrepancies between the morphological and genetic identification were observed, demonstrating the effectiveness of using different molecular markers for the correct identification of these hybrids. The necessity of implementation of management and conservation projects to maintain the genetic integrity of native species populations threatened by hybridization in the rivers of Mato Grosso do Sul State is evident.